The Functions of the HIV1 protein Vpr and its action through the DCAF1•DDB1•Cullin4 ubiquitin ligase - Casey, Laurieann (2010)
Among the proteins encoded by human and simian immunodeficiency viruses (HIV and SIV) at least three, Vif, Vpu and Vpr, subvert cellular ubiquitin ligases to block the action of anti-viral defenses. This review focuses on Vpr and its HIV2/SIV counterparts, Vpx and Vpr, which all engage the DDB1•Cullin4 ubiquitin ligase complex through the DCAF1 adaptor protein. Here, we discuss the multiple functions that have been linked to Vpr expression and summarize the current knowledge on the role of the ubiquitin ligase complex in carrying out a subset of these activities.